Foliar Nitrogen Application Enhances Nitrogen Assimilation and Modulates Gene Expression in Spring Wheat Leaves - Yanlin Yao; Wenyan Ma; Xin Jin; Guangrui Liu; Yun Li; Baolong Liu; Dong Cao (Agronomy, 2025)
Nitrogen (N) critically regulates wheat growth and grain quality, yet the molecular mechanisms underlying foliar nitrogen application remain unclear. This study evaluated the effects of foliar nitrogen application (12.25 kg ha−1) on the growth, grain yield, and quality of spring wheat, as well as its molecular mechanisms. The results indicated that N was absorbed within 3 h post-application, with leaf nitrogen concentration peaking at 12 h. The N treatment increased whole-plant dry matter accumulation and grain protein content by 11.34% and 6.8%, respectively. Amino acid content peaked 24 h post-application, increasing by 25.3% compared to the control. RNA-sequencing analysis identified 4559 and 3455 differentially expressed genes at 3 h and 24 h after urea treatment, respectively, these DEGs being primarily involved in nitrogen metabolism, photosynthetic carbon fixation, amino acid biosynthesis, antioxidant systems, and nucleotide biosynthesis. Notably, the plastidic glutamine synthetase gene (GS2) is crucial in the initial phase of urea application (3 h post-treatment). The pronounced downregulation of GS2 initiates a reconfiguration of nitrogen assimilation pathways. This downregulation impedes glutamine synthesis, resulting in a transient accumulation of free ammonia. In response to ammonia toxicity, the leaves promptly activate the GDH (glutamate dehydrogenase) pathway to facilitate the temporary translocation of ammonium. This compensatory mechanism suggests that GS2 downregulation may be a key switch that redirects nitrogen metabolism from the GS/GOGAT cycle to the GDH bypass. Additionally, the upregulation of the purine and pyrimidine metabolic routes channels nitrogen resources towards nucleic acid synthesis, and thereby supporting growth. Amino acids are then transported to the seeds, culminating in enhanced seed protein content. This research elucidates the molecular mechanisms underlying the foliar response to urea application, offering significant insights for further investigation.